Catalytic electrooxidation of formic acid by noble metal nanoparticle catalysts on reduced graphene oxide - Suwaphid Themsirimongkon (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. The noble metals (Pt and Pd) loaded on polydopamine (PDA) modified graphene oxide (GO) as catalysts were prepared by a reduction. The catalysts were characterized by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The reduced graphene oxide (rGO) was prepared for use as a matrix to integrate alloyed metal catalysts. The results show that the dispersed small-catalyst nanoparticles are loaded on both GO and rGO supports and the PtxPdy catalysts on rGO are smaller than the PtxPdy catalysts on GO. Both cyclic voltammetry (CV) and chronoamperometry (CA) results reveal that bimetallic PtxPdy/PDA-GO catalysts have superior activity, CO tolerance, electron transfer and stability towards formic acid oxidation, compared to PtxPdy/GO and the commercial PtRu/C catalyst. The bimetallic PtxPdy and PDA loaded on GO could be capable of enhanced oxidation and hopefully used in direct formic acid fuel cells.